Evaluation of Antioxidant Property in Secondary Metabolites Isolated from Sargassum wightii Collected From Kanyakumari Coastal Region, Tamilnadu.: Life Sciences-Biotechnology - Vellingiri Manon Mani; Selvam Nivethitha; Kathirvel Preethi; A. Parimala Gnana Soundari; V. Subha Priya; P. Deepak; M. P. Ayyappa Das (International Journal of Life Science and Pharma Research, 2022)
The demands for increasing anticancer drugs produced by natural sources with potential antioxidant and antimicrobial properties had led the path to mass production in pharmaceutical fields. This current investigation is implied to extract the potential crude secondary metabolites extract from brown algae Sargassum wightii Greville ex J.Agardh with maximum antimicrobial and antioxidant properties. The brown seaweed was collected from Kanyakumari, Tamil Nadu, India and taken for extraction process using various polar and non-polar solvents. The solvents which extracted maximum crude metabolites were taken to determine the preliminary antimicrobial analysis using clinical pathogens on which the crude extracts explored the highest zone of inhibition at least concentration. Further, the five different crude extracts were subjected to antioxidant assessment and the extract in different solvents manifested maximum activity at minimum concentration. The results of antimicrobial and antioxidant analysis evinced that the ethyl acetate and methanolic extract exhibited maximum activity when compared to other crude extracts. The extract which explored the highest activity was taken for qualitative and quantitative phytochemical determination and both the extract showed the presence of most of the phytochemicals. Further, the investigation is carried out to purify and determine the anticancer property in cancer cell lines.